Comparative study of induced changes in effective lens position and refraction after Nd:YAG laser capsulotomy according to intraocular lens design - Monteiro, Tiago (2018)
To evaluate and compare the changes in refraction and effective intraocular lens (IOL) position between a plate-haptic IOL and a c-loop single-piece IOL after neodymium-doped yttrium aluminium garnet (YAG) laser posterior capsulotomy.